Microelement composition of oral fluid in patients with chronic cerebral ischemia - A. V. Mitronin; M. Yu. Maksimova; D. A. Ostanina; O. A. Antonova (Эндодонтия Today)
Relevance. Today, due to the emergence of new and improvement of existing methods of laboratory diagnostics, more and more attention of researchers is directed to the study of the composition and properties of the oral fluid of a person with a history of somatic diseases.  Aim. To study the microelement composition of the oral fluid of patients with chronic cerebral ischemia and compare the obtained data with clinical parameters.  Materials and methods. The paper presents the results of a clinical and laboratory study of 26 patients with chronic cerebral ischemia. In the course of an objective examination, the following were carried out determination of the KPU index, Greene-Wermillion hygienic index, salivation rate and pH of the oral fluid. The concentration of microelements in the oral fluid was studied by the method of emission spectral analysis (ICP-AES), the activity of alkaline phosphatase activity was studied by the Bessie-Lowry-Brock endpoint method. Statistical processing of the results was carried out using the computer program Statistica 10.0.  Results. According to the results of the study in the oral fluid of patients with chronic cerebral ischemia, a change in the concentration of five microelements was established. An increase for Ca (87.19 ± 2.45, p < 0.001), K (1283.73 ± 79.36, p < 0.001) and Mo (0.007 ± 0.0005, p < 0.001) and a decrease in the level of Na (672.30 ± 47.30, p < 0.05) and Fe (0.23 ± 0.07, p < 0.05) in comparison with patients of the control group. In addition, a significant increase in ALP activity in the oral fluid of patients with chronic cerebral ischemia was revealed.  Conclusions. The obtained results of clinical and laboratory studies confirm that in patients with chronic cerebral ischemia, changes in the microelement composition of the oral fluid are noted, which leads to the development of pathological processes in the oral cavity.